Morfologi dan morfometri kelelawar Hipposideros larvatus penghuni Gua Pemetung Bengkulu Utara - Fadhlullah, Muhammad Farid; Sari, Armanda Okta Pramita; Sari, Rosi Triana; Pasaribu, Marta Royana BR; Nurul Kamilah, Santi (Filogeni: Jurnal Mahasiswa Biologi, 2024)
Pemetung Cave is located in Padang Bendar Village, North Bengkulu Regency, surrounded by dense foliage with a river flowing near the cave. Based on surveys, the cave is inhabited by a colony of bats, and this research is important because bats have an ecological role in maintaining the balance of the cave ecosystem. This study aims to inventory the types of bats inhabiting Pemetung Cave. The research was conducted using observation methods and direct bat capture within the cave using hand nets. The results showed 15 adult bats and 2 juvenile bats, consisting of 6 males and 11 females. Identification based on morphological characteristics indicated that all the bats were of the species Hipposideros larvatus. Morphometric measurements ranged from 40.4-76.0 mm for body length (HB), 47.7 mm for total body length (TL), 8.9-29.4 mm for tibia length (T), 32.5-64.6 mm for forearm length (FA), 7.3-21.4 mm for ear length (E), and 7.3-14.1 mm for hindfoot length (HF). Pemetung Cave provides a good shelter for Hipposideros larvatus bats, thus serving as a roosting site.